Battery
By adding additive B with the structure of formula I to the electrolyte of the lithium-ion battery, and controlling the relationship between its mass content and the powder conductivity of the negative electrode active material layer, the problem of intensifying side reactions of the electrolyte is solved, and the fast charging performance and high-temperature cycle life of the battery are improved.
Patent Information
- Application Number
- CN202510116753.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-24
AI Technical Summary
In the process of increasing the voltage of lithium-ion batteries to improve circulation performance, the side reactions in the electrolyte are intensified, causing serious gas production of the battery and affecting its performance.
Add additive B with the structure of formula I to the electrolyte, and ensure that its mass content and the powder conductivity of the negative electrode active material layer meet a specific relationship (6.5≤a/b≤550) to reduce the degree of side reaction of the electrolyte.
By reducing the side reactions of the electrolyte, the gas production of the battery during use is reduced, and the fast charging performance and high-temperature cycle life of the battery are improved.
Smart Images

Figure BDA0005258010210000011 
Figure BDA0005258010210000021 
Figure BDA0005258010210000041
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries, and in particular relates to a battery. Background Art
[0002] Lithium-ion batteries are developing rapidly, and lithium-ion batteries with higher energy density have become the future trend. While pursuing lithium-ion batteries with higher energy density, the requirements for cycle performance are becoming higher and higher.
[0003] As the requirements for cycle performance become increasingly higher, the battery voltage needs to be increased. However, as the voltage increases, the side reactions of the solvents, additives and other components in the electrolyte will be accelerated, resulting in serious gas production in the battery. At the same time, hydrofluoric acid will be produced, which will reduce the cycle performance of the ion battery and seriously affect the performance of the ion battery. Summary of the invention
[0004] In view of this, an object of the present invention is to provide a battery, wherein the battery assembled with the electrolyte has excellent cycle performance.
[0005] The present invention provides a battery, comprising an electrolyte and a negative electrode;
[0006] The electrolyte includes an additive B having a structure of Formula I:
[0007]
[0008] R1, R2 and R3 are independently selected from -H or -C p H 2p+1 , where 1≤p≤4;
[0009] R4, R5 and R6 are independently selected from vinyl, allyl, oxyvinyl, oxyallyl, oxyallyl, alkynylethyl, propargyl, oxyalkynylethyl or oxypropargyl;
[0010] R7, R8 and R9 are independently selected from -H, -CH3 or -CH2CH3;
[0011] The negative electrode includes a negative electrode active material layer;
[0012] The powder conductivity of the negative electrode active material layer is a, in units of S / cm;
[0013] Based on the mass of the electrolyte, the mass content of additive B is b%, and a and b satisfy the relationship:
[0014] 6.5≤a / b≤550.
[0015] The above-mentioned battery provided by the present invention adds only an additive B having a structure of Formula I into the electrolyte. Based on the mass of the electrolyte, the mass content of the additive B is b%, and the additive B satisfies the following relationship with the powder conductivity a of the negative electrode active material layer in the negative electrode: 6.5≤a / b≤550. When the relationship is satisfied, the degree of side reaction of the electrolyte is low, reducing the gas production of the battery during use, thereby improving the fast charging performance and high-temperature cycle life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 The graph is a cycle capacity retention rate graph of the batteries prepared in Example 1 of the present invention and Comparative Example 7 at 60°C. DETAILED DESCRIPTION
[0017] The present invention provides a battery, comprising an electrolyte and a negative electrode;
[0018] The electrolyte includes an additive B having a structure of Formula I:
[0019]
[0020] R1, R2 and R3 are independently selected from -H or -C p H 2p+1 , where 1≤p≤4;
[0021] R4, R5 and R6 are independently selected from vinyl, allyl, oxyvinyl, oxyallyl, oxyallyl, alkynylethyl, propargyl, oxyalkynylethyl or oxypropargyl;
[0022] R7, R8 and R9 are independently selected from -H, -CH3 or -CH2CH3;
[0023] The negative electrode includes a negative electrode active material layer;
[0024] The powder conductivity of the negative electrode active material layer is a, in units of S / cm;
[0025] Based on the mass of the electrolyte, the mass content of additive B is b%, and a and b satisfy the relationship:
[0026] 6.5≤a / b≤550.
[0027] The present invention only adds additive B having the structure of formula I into the electrolyte, and when the conductivity of the powder of the negative electrode active material layer in the negative electrode satisfies a certain relationship, the side reaction degree of the electrolyte is low, thereby reducing the gas production of the battery during use, thereby improving the fast charging performance and high-temperature cycle life of the battery.
[0028] In the present invention, R1, R2 and R3 are all selected from -H, and R4, R5 and R6 are independently selected from alkynylethyl, propargyl, oxyalkynylethyl or oxypropargyl.
[0029] R1, R2 and R3 are all selected from -C p H 2p+1 , then R4, R5 and R6 are independently selected from vinyl or oxyethylene.
[0030] The powder conductivity of the negative electrode active material layer described in the present invention is a, and the mass content of the additive B is b%, and a and b satisfy the relationship: 0.1≤a / b≤40; the addition of additive B can effectively reduce the gas production of the electrolyte under high voltage, improve the high voltage resistance of the electrolyte, thereby improving the high temperature life of the battery, and at the same time, because the powder conductivity of the negative electrode active material and the addition amount of additive B satisfy the relationship, the higher powder conductivity of the negative electrode active material can improve the conductivity of the negative electrode active material layer, so that the DCR of the entire battery system is controlled within a reasonable range, so that the battery has excellent fast charging capability.
[0031] The powder conductivity a of the negative electrode active material layer in the present invention is 5 to 20 S / cm, preferably 8 to 18 S / cm. In specific embodiments, the powder conductivity is 13.41 S / cm, 17.95 S / cm, 8.02 S / cm, 8.01 S / cm, 10.45 S / cm, 7.9 S / cm, 18.12 S / cm, 17.88 S / cm, 10.21 S / cm, 8.21 S / cm, 11.21 S / cm, 18.97 S / cm, 5.03 S / cm, 6.05 S / cm, 19.68 S / cm, 12.61 S / cm, 12.89 S / cm, 13.22 S / cm, 12.51 S / cm, 13.23 S / cm, 8.02 S / cm, 9.13 S / cm, 10.34 S / cm, 12.75 S / cm, 11.98 S / cm, 8.01 S / cm, 9.02 S / cm, 11.03 S / cm, 12.71 S / cm, 11.41 S / cm, 12.23 S / cm or 14.41 S / cm.
[0032] Based on the mass of the electrolyte, the mass content of the additive B in the present invention is b%, 0.01%≤b≤3%, preferably 0.1% to 1.5%. In a specific embodiment of the present invention, the mass content b of the additive B is 0.85%, 1.491%, 0.841%, 0.105%, 0.102%, 1.121%, 1.452%, 1.521%, 0.112%, 0.913%, 0.105%, 2.330%, 0.711%, 0.011%, 2.995%, 0.750%, 0.122%, 0.812%, 0.332%, 1.492%, 1.495%, 0.102%, 0.824%, 0.354%, 1.491% or 1.413%.
[0033] In the present invention, the relational expression satisfied by a and b is 6.5 ≤ a / b ≤ 550, preferably 9.5 to 102.5; in specific embodiments, the value of a / b is 15.78, 12.04, 9.54, 76.29, 102.45, 65.29, 12.48, 11.76, 91.16, 8.99, 106.76, 8.14, 7.07, 550, 6.57, 16.81, 17.19, 17.63, 16.68, 17.64, 65.74, 11.24, 31.14, 8.55, 8.01, 78.53, 10.95, 31.16, 8.52, 8.08, 16.31 or 19.21.
[0034] In the additive B having the structure of Formula I provided by the present invention, the number of double bonds is n, and the value range of n is 1 to 5; n is a positive integer; it can be 1, 2, 3, 4 or 5; preferably 2 to 3. When the double bond content of the additive B is within this content range, the achieved effect is that a dense SEI can be formed after reduction at the negative electrode to play a role in protecting the negative electrode interface, and the electrolyte will not have a large impedance and will not affect the kinetic performance of the battery.
[0035] The specific structure of Formula I in the present invention includes Formulas (I1) to (I21):
[0036]
[0037]
[0038] The battery provided by the present invention further includes a positive electrode;
[0039] The positive electrode includes a positive electrode main material, a binder, and a conductive agent;
[0040] The positive electrode main material is lithium iron phosphate or ternary material or lithium manganese iron phosphate.
[0041] In the positive electrode of the present invention, the mass ratio of the positive electrode main material, the binder, and the conductive agent is (97 to 98):(1 to 1.5):(0.8 to 1.2); in specific embodiments, the mass ratio of the main material, the binder, and the conductive agent in the positive electrode is 97.8:1.2:1.
[0042] In the present invention, the structural formula of the ternary material used in the positive electrode main material is LiNi x1 Co y Mn 1-x1-y O2 (0 < x1 < 1, 0 < y < 1). The structural formula of the lithium manganese iron phosphate used is LiMn x2 Fe (1-x2) PO4 (0 < x2 < 1). In specific embodiments, the ternary material is LiNi 0.4 Co 0.2 Mn0.4 O2; The lithium iron manganese phosphate is LiMn 0.4 Fe 0.6 PO4.
[0043] The battery provided by the present invention further includes a negative electrode,
[0044] The negative electrode includes a negative electrode main material, a binder, and a conductive agent,
[0045] The particle size Dv50 of the negative electrode main material ranges from 5 to 20 μm; the negative electrode main material is selected from one or more of natural graphite, artificial graphite, mesophase carbon microspheres, hard carbon, soft carbon, silicon oxide, silicon carbon, and Li4Ti5O 12 among others.
[0046] In the negative electrode of the present invention, the mass ratio of the negative electrode main material, the binder, and the conductive agent is (96 - 98.5):(1.0 - 2.5):(0.5 - 1.5); in a specific embodiment, the mass ratio of the negative electrode main material, the binder, and the conductive agent in the negative electrode is 97.5:1.2:1.3.
[0047] The preparation method of the positive electrode sheet in the present invention:
[0048] The positive electrode main material, the binder, and the conductive agent are dispersed in N-methylpyrrolidone (NMP) according to a mass ratio of (95.5 - 98.2):(1 - 2.0):(0.8 - 2.5). The positive electrode slurry is coated on an aluminum foil to obtain an aluminum foil with the positive electrode slurry coated on its surface, and then roll-pressed and cut to obtain the positive electrode sheet.
[0049] In a specific embodiment, the mass ratio of the positive electrode main material, the binder, and the conductive agent is 97.8:1.2:1.
[0050] The positive electrode main material is lithium iron phosphate (the particle size Dv50 ranges from 0.1 to 2 μm), lithium nickel cobalt manganese oxide (the particle size Dv50 ranges from 3 to 15 μm), and the structural formula is LiNi x1 Co y Mn 1-x1-y O2 (0 < x1 < 1, 0 < y < 1), lithium iron manganese phosphate (the particle size D50 ranges from 3 to 5 μm), and the structural formula is LiMn x2 Fe (1-x2) PO4 (0 < x2 < 1) or any one of them.
[0051] When the positive electrode material is lithium iron phosphate, the compaction density on one side of the positive electrode sheet is 2.2 - 2.6 g / cm 3 , when the positive electrode material is lithium nickel cobalt manganese oxide, the compaction density on one side of the positive electrode sheet is 3.2 - 3.8 g / cm 3 , when the positive electrode material is lithium iron manganese phosphate, the compaction density on one side of the positive electrode sheet is 2.4 - 2.8 g / cm 3 .
[0052] The binder is selected from polytetrafluoroethylene or PVDF.
[0053] The conductive agent is selected from one or more of conductive carbon black, acetylene black and carbon nanotubes.
[0054] The preparation method of the negative electrode sheet described in the present invention:
[0055] The negative electrode main material, the binder and the conductive agent are dispersed in deionized water according to a mass ratio of (96-98.5):(1.0-2.5):(0.5-1.5), and the negative electrode slurry is coated on a copper foil; then, the negative electrode sheet is obtained by rolling and cutting.
[0056] The compaction density of the negative electrode sheet is 1.4-1.8 g / cm 3 In the embodiment, the compaction density of the negative electrode sheet is 1.6 g / cm 3 .
[0057] The negative electrode main material is selected from natural graphite, artificial graphite, mesophase carbon microspheres, hard carbon, soft carbon, silicon oxygen, silicon carbon and Li4Ti5O 12 One or more of; the negative electrode main material of the negative electrode sheet of the present invention is selected from natural graphite, artificial graphite, mesophase carbon microspheres, hard carbon, soft carbon, silicon oxygen, silicon carbon and Li4Ti5O 12 One or more of; In a specific embodiment, the negative electrode main material is artificial graphite. The Dv50 of the negative electrode main material is 5-20μm, and Dv50 can specifically be 5μm, 5.5μm, 6.0μm, 6.5μm, 7.0μm, 7.5μm, 8.0μm, 8.5μm, 9.0μm, 9.5μm, 10.0μm, 10.5μm, 11.0μm, 11.5μm, 12.0μm, 12.5μm, 13.0μm, 13.5μm, 14.0μm, 14.5μm, 15.0μm, 15.5μm, 16.0μm, 16.5μm, 17.0μm, 17.5μm, 18.0μm, 18.5μm, 19.0μm, 19.5μm or 20μm. In a specific embodiment, the Dv50 of the negative electrode active material is 10.5μm, 7.6μm, 17.2μm, 17.1μm, 12.2μm, 17.4μm, 7.3μm, 7.7μm, 12.8μm, 10.5μm, 6.4μm, 19.8μm, 18.3μm, 5.2μm, 11.4μm, 11.2μm, 10.9μm, 11.6μm, 15.1μm, 12.3μm, 11.3μm, 12μm, 17.2μm, 15.2μm, 12.4μm, 11.3μm, 12.1μm, 11.6μm or 9.4μm, and the main material of the negative electrode is artificial graphite.
[0058] The binder is selected from one or more of polyacrylic acid (PAA), styrene-butadiene rubber (SBR) and carboxymethyl cellulose (CMC);
[0059] The conductive agent is selected from one or more of conductive carbon black and carbon nanotubes.
[0060] The preparation method of the electrolyte described in the present invention:
[0061] The solvent and the lithium salt are mixed to prepare a mixed solution with a lithium salt concentration of 0.5 to 1.5 mol / L, and the additive B is added and mixed to obtain an electrolyte.
[0062] The solvent includes, but is not limited to, at least one of ethylene carbonate (EC), methylene methanedisulfonate (MMDS), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), propylene carbonate (PC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), cyclopentane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS), and diethyl sulfone (ESE). In a specific embodiment, the solvent is obtained by mixing ethylene carbonate and ethyl methyl carbonate in a mass ratio of 3:7.
[0063] The lithium salt includes, but is not limited to, at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP), and lithium tetrafluorooxalatophosphate (LiTFOP). In a specific embodiment, the concentration of the lithium salt is 1 mol / L.
[0064] In the present invention, the separator is selected from PP, PE, and PP / PE.
[0065] The present invention preferably prepares the above-mentioned battery according to the following method:
[0066] Prepare positive electrode sheets and negative electrode sheets respectively;
[0067] The solvent and the lithium salt are mixed to prepare a mixed solution with a lithium salt concentration of 0.5 to 1.5 mol / L, and the additive B is added and mixed to obtain an electrolyte;
[0068] Stack the positive electrode sheet, the separator, and the negative electrode sheet in order, and wind them up to obtain a bare battery cell;
[0069] The bare battery cell is placed in an outer packaging shell, and after drying, an electrolyte is injected, and a lithium ion battery is obtained through vacuum packaging, liquid injection, standing, formation and constant volume.
[0070] The present invention has no special limitation on the processes of vacuum packaging, liquid injection, standing, forming, and volume determination, and any process known to those skilled in the art may be adopted.
[0071] In order to further illustrate the present invention, a battery provided by the present invention is described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0072] Examples 1 to 30 and Comparative Examples 1 to 4
[0073] Refer to Table 1 and Table 2 for the types of raw materials and the values of raw material parameters:
[0074] A method for preparing a battery, comprising:
[0075] 1) Preparation of positive electrode:
[0076] The positive electrode main material lithium iron phosphate, the binder PVDF, and the conductive agent SP are dispersed in N-methylpyrrolidone (NMP), and the positive electrode slurry is coated on an aluminum foil to obtain an aluminum foil with the positive electrode slurry coated on the surface; then, the positive electrode sheet is obtained by rolling and cutting, and the compaction density of one side of the positive electrode sheet is controlled to be 2.3g / cm 3 .
[0077] 2) Method for preparing the negative electrode sheet:
[0078] The negative electrode main material artificial graphite, binder SBR, and conductive agent SP are dispersed in deionized water, and the negative electrode slurry is coated on the copper foil to obtain the copper foil with the negative electrode slurry coated on the surface to obtain the negative electrode sheet, and the compaction density of one side of the negative electrode sheet is controlled to be 1.6 g / cm 3 ;
[0079] 3) Preparation method of the electrolyte:
[0080] The solvent and the lithium salt are mixed to prepare a mixed solution with a lithium salt concentration of 1 mol / L, and the additive B is added and mixed to obtain an electrolyte;
[0081] The solvent is obtained by mixing ethylene carbonate and ethyl methyl carbonate in a mass ratio of 3:7; the lithium salt is lithium hexafluorophosphate.
[0082] 4) Isolation film: Choose PP as the isolation film;
[0083] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order and wound to obtain a bare battery cell;
[0084] The bare battery cell is placed in an outer packaging shell, and after drying, an electrolyte is injected, and a lithium ion battery is obtained through vacuum packaging, liquid injection, standing, formation and constant volume.
[0085] Embodiment 31
[0086] Compared with Example 1, in addition to the differences listed in Table 1, the differences also include: the positive electrode main material used is ternary LiNi 0.4 Co 0.2 Mn 0.4 O2; the compaction density of one side of the positive electrode is 3.3g / cm 3 .
[0087] Embodiment 32
[0088] Compared with Example 1, in addition to the differences listed in Table 1, the differences also include: the main material of the positive electrode is lithium manganese iron phosphate LiMn 0.4 Fe 0.6 PO4; the compaction density of one side of the positive electrode is 2.6g / cm 3 .
[0089] Comparative Example 5
[0090] Compared with Comparative Example 1, in addition to the differences listed in Table 2, the differences also include: the positive electrode main material used is ternary LiNi 0.4 Co 0.2 Mn 0.4 O2; the compaction density of one side of the positive electrode is 3.3g / cm 3 .
[0091] Comparative Example 6
[0092] Compared with Comparative Example 1, in addition to the differences listed in Table 2, the differences also include: the main material of the positive electrode is lithium iron manganese phosphate LiMn 0.4 Fe 0.6 PO4; the compaction density of one side of the positive electrode is 2.6g / cm 3 .
[0093] Comparative Example 7
[0094] Compared with Example 1, additive B is not added, and the rest is the same as Example 1. The battery performance results prepared in the above examples and comparative examples are shown in Table 3:
[0095] Table 1
[0096]
[0097] Table 2
[0098]
[0099] Table 3
[0100]
[0101]
[0102] Test method:
[0103] 1. Test method for additive B content:
[0104] Use battery charging and discharging equipment to discharge the battery. The discharge conditions are as follows: current 0.3C, cut-off voltage 2.5V. After recording the battery number / barcode, disassemble the battery in a glove box (H2O≤0.1ppm, O2≤0.1ppm) to collect the electrolyte.
[0105] There are two ways to collect electrolyte: After removing the battery cover, ① if there is free electrolyte, use a pipette to collect the electrolyte into a 5mL sample tube and seal it with sealing glue to prevent electrolyte leakage. ② if there is no free electrolyte, use a hydraulic press (Beijing Hengaode Technology Co., Ltd. FY-30 hydraulic press) to continuously pressurize until free electrolyte appears, collect the electrolyte into the sample tube and seal it.
[0106] The collected electrolyte samples were injected into the Agilent Intuvo 9000 gas chromatograph-mass spectrometer using a microinjector for content testing:
[0107] ① Obtaining the MS standard curve and LC peak area-concentration curve: Formula I1 to Formula I21 are prepared into EMC solutions of different concentrations, and injected into the above-mentioned liquid chromatography-mass spectrometer, respectively, to obtain the MS spectrum and LC spectrum of the standard substance, and the peak area in the LC spectrum is integrated (the test software performs routine processing on the test data) to obtain the peak area. A linear graph is drawn between the peak area and concentration of the standard substance of different concentrations to obtain a standard LC peak area-concentration curve.
[0108] ② Determination of the type: Inject the electrolyte to be tested into the above-mentioned liquid chromatography-mass spectrometer to obtain the LC spectrum and MS spectrum of the electrolyte to be tested. Compare the MS spectrum of the electrolyte to be tested with the MS spectrum of the standard to determine whether the electrolyte to be tested contains additives of formula I1 to I21 (for example, if the MS spectrum of the electrolyte to be tested has a corresponding peak at the position of the peak of formula I1 in the standard spectrum, it is determined that the electrolyte to be tested contains additive B of formula I1, and the same applies to other components).
[0109] ③Determination of quality content:
[0110] The peak area is obtained by integrating the peaks in the LC spectrum of the electrolyte to be tested. According to the standard LC peak area-concentration curve, the concentration of the substance to be tested can be obtained if the peak area is known.
[0111] 2. Test method for the number of double bonds in additive B:
[0112] Use battery charging and discharging equipment to discharge the battery. The discharge conditions are as follows: current 0.3C, cut-off voltage 2.5V. After recording the battery number / barcode, disassemble the battery in a glove box (H2O≤0.1ppm, O2≤0.1ppm) to collect the electrolyte.
[0113] There are two ways to collect electrolyte: After removing the battery cover, ① if there is free electrolyte, use a pipette to collect the electrolyte into a 5mL sample tube and seal it with sealing glue to prevent electrolyte leakage. ② if there is no free electrolyte, use a hydraulic press (Beijing Hengaode Technology Co., Ltd. FY-30 hydraulic press) to continuously pressurize until free electrolyte appears, collect the electrolyte into the sample tube and seal it.
[0114] Experimental process:
[0115] 1) Weigh an appropriate amount of electrolyte sample into a 250ml iodine volumetric flask, add 20g deionized water, then add 5ml acetone, shake well to dissolve. Continue to add 10ml potassium bromide-potassium bromate solution and 5ml hydrochloric acid solution, cover the bottle cap and place it in a dark place for 20 minutes, then add 10ml potassium iodide solution, cover the bottle cap and place it for 20 minutes.
[0116] 2) The blank sample is the same as step 1 above, but no electrolyte sample to be tested is added
[0117] 3) Titrate the samples obtained in step 1 and step 2 respectively with sodium thiosulfate standard solution. Titrate until the sample turns light yellow, then add 2-3 drops of starch indicator and titrate until colorless. End the titration and record the amount of sodium thiosulfate standard solution used for the sample obtained in step 1, recorded as V; record the amount of sodium thiosulfate standard solution used for the sample obtained in step 2, recorded as V0.
[0118] The number of double bonds in the additive in the electrolyte sample is calculated according to formula (1):
[0119]
[0120] Wherein, n: the number of double bonds contained in additive B;
[0121] c: concentration of Na2S2O3, unit: mol / L;
[0122] V: the amount of Na2S2O3 required to titrate m grams of electrolyte sample, unit L;
[0123] V0: the amount of Na2S2O3 required to titrate the blank sample, unit L;
[0124] m: mass of electrolyte sample, in g;
[0125] b: The amount of additive B added to the electrolyte sample, unit: %.
[0126] Preparation of required solution:
[0127] 0.09 mol / L potassium bromate-potassium bromide solution (i.e., potassium bromide concentration is 0.09 mol / L): 2.8 g potassium bromate and 10 g potassium bromide are dissolved in a small amount of deionized water and diluted to 1000 mL;
[0128] 0.1 mol / L sodium thiosulfate standard solution (greatest impact on the experiment, standard sample titration or purchase);
[0129] 10% potassium iodide solution: 10g potassium iodide dissolved in 90g deionized water;
[0130] 1% starch indicator: 1g soluble starch is dissolved in 99g deionized water, heated to boiling and clarified, and after cooling, 0.125g benzoic acid is added for preservation;
[0131] 1:1 hydrochloric acid: Mix equal volumes of deionized water and 36% hydrochloric acid;
[0132] 3. Test method for the powder conductivity of the negative electrode active material layer:
[0133] 1) Discharge: After recording the battery number / barcode, use the battery charging and discharging equipment to discharge the battery. Discharge conditions: current 0.3C, cut-off voltage 2.5V;
[0134] 2) Disassembly and cleaning: Disassemble the battery in a room with dew point control, take out the negative electrode sheet, soak the negative electrode sheet in a polytetrafluoroethylene box filled with DMC solvent for 24 hours, then take out the negative electrode sheet, bake the cleaned electrode sheet at 60°C for 4 hours to remove the residual DMC solvent, and obtain the electrode sheet to be tested;
[0135] 3) Scraping powder: Scrape the electrode for powder treatment, use a mortar to gently grind the scraped powder to eliminate lumps in the powder, and collect the powder for testing;
[0136] 4) Testing: The collected powder samples were placed in the sample cell of a YK22-FT-300II powder conductivity meter to test the conductivity and obtain the powder conductivity of the negative electrode active material layer.
[0137] 4. Test method for negative electrode particle size
[0138] 1) Discharge: After recording the battery number / barcode, use the battery charging and discharging equipment to discharge the battery. Discharge conditions: current 0.3C, cut-off voltage 2.5V;
[0139] 2) Disassembly and cleaning: Disassemble the battery in a room with dew point control, take out the negative electrode sheet, soak the negative electrode sheet in a polytetrafluoroethylene box filled with DMC solvent for 24 hours, then take out the negative electrode sheet, bake the cleaned electrode sheet to remove the residual DMC solvent, and obtain the electrode sheet to be tested;
[0140] 3) Scraping powder: Scrape the electrode for powder treatment, use a mortar to gently grind the scraped powder to eliminate lumps in the powder, and collect the powder for testing;
[0141] 4) Testing: The particle size of the negative electrode particles was tested using a scanning electron microscope.
[0142] 5. Fast charging performance test method
[0143] After recording the battery number / barcode, use a battery charge and discharge device to discharge the battery. The discharge conditions are: current 0.33C, cut-off voltage 2.5V, and then use 0.33C for charge and discharge cycles. The lower and upper voltage limits are 2.5V and 3.65V respectively. Charge and discharge for 3 cycles to determine the capacity, and use the discharge capacity of the third cycle as the battery capacity. Then after charging to 5% SOC with 0.33C, a fast charging test was carried out, specifically: charging to 10% SOC at 1.5C, recording the charging time of this stage as t1, charging to 20% SOC at 1.5C, recording the charging time of this stage as t2, standing for 5 minutes, charging to 30% SOC at 1.5C, recording the charging time of this stage as t3, standing for 5 minutes, charging to 40% SOC at 1.5C, recording the charging time of this stage as t4, standing for 5 minutes, charging to 50% SOC at 1.5C, recording the charging time of this stage as t5, standing for 5 minutes, then charging to 60% SOC at 1.2C, recording the charging time of this stage as t6, standing for 5 minutes, charging to 70% SOC at 1.2C, recording the charging time of this stage as t7, standing for 5 minutes, charging to 80% SOC at 1.2C, recording the charging time of this stage as t8, standing for 5 minutes. Fast charging time t=t1+t2+t3+t4+t5+t6+t7+t8. The shorter the fast charging time, the better the fast charging performance of the battery.
[0144] 6. Test method for cycle capacity retention at 60°C
[0145] The LAND system was used to test the cycle performance of lithium-ion batteries. The temperature of the equipment was adjusted so that the temperature of the LAND system was at 60°C. The batteries were charged to 3.65V at a charging rate of 0.5C, with a cut-off current of 0.05C. After standing for 10 minutes, the batteries were discharged to 2.5V at a discharge rate of 1C and stood for 10 minutes. Under this condition, the battery was charged and discharged for 280 cycles. The discharge capacity Q1 of the first cycle and the discharge capacity Q2 of the 280th cycle were recorded. The capacity retention rate of the battery after 280 cycles was calculated according to the formula Q2 / Q1×100%.
[0146] As can be seen from the above embodiments, the present invention provides the above-mentioned battery provided by the present invention, by adding only additive B having the structure of formula I into the electrolyte, taking the mass of the electrolyte as the reference, the mass content of additive B is b%, and the powder conductivity a of the negative electrode active material layer in the negative electrode satisfies the following relationship: 6.5≤a / b≤550. When the relationship is satisfied, the side reaction degree of the electrolyte is low, reducing the gas production of the battery during use, thereby improving the fast charging performance and high temperature cycle life of the battery. The experimental results show that the fast charging time of the battery is 22 to 29 minutes; at 60°C, the lithium-ion battery has a capacity retention rate of 80 to 89% after 280 cycles at a charge and discharge rate of 0.5C / 1C, a current cutoff of 0.05C, and a voltage range of 2.5-3.65V.
[0147] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A battery comprising an electrolyte and a negative electrode; The electrolyte includes an additive B having a structure of Formula I: R1, R2 and R3 are independently selected from -H or -C p H 2p+1 ,in, 1≤p≤4; R4, R5 and R6 are independently selected from vinyl, allyl, oxyvinyl, oxyallyl, oxyallyl, alkynylethyl, propargyl, oxyalkynylethyl or oxypropargyl; R7, R8 and R9 are independently selected from -H, -CH3 or -CH2CH3; The negative electrode includes a negative electrode active material layer; The powder conductivity of the negative electrode active material layer is a, in units of S / cm; Based on the mass of the electrolyte, the mass content of additive B is b%, and a and b satisfy the relationship: 6.5≤a / b≤550.
2. The battery according to claim 1, characterized in that 5≤a≤20, preferably 8-18.
3. The battery according to claim 1, characterized in that 0.01%≤b%≤3%, preferably 0.1% to 1.5%.
4. The battery according to claim 1, characterized in that 9.5≤a / b≤102.
5.
5. The battery according to claim 1, characterized in that R1, R2 and R3 are all selected from -H, and R4, R5 and R6 are independently selected from alkynylethyl, propargyl, oxyalkynylethyl or oxypropargyl.
6. The battery according to claim 1, characterized in that R1, R2 and R3 are all selected from -C p H 2p+1 , then R4, R5 and R6 are independently selected from vinyl or oxyethylene.
7. The battery according to claim 1, characterized in that The specific structural formulas (Ⅰ1) to (Ⅰ21) of the formula Ⅰ are:
8. The battery according to claim 1, characterized in that The number of double bonds in the additive B having the structure of formula I is n, and the value range of n is 1-5.
9. The battery according to claim 8, characterized in that The value range of n is 2 to 3, 8.5≤a / b≤31.
2.
10. The battery according to claim 1, characterized in that The negative electrode active material layer comprises a negative electrode main material, the particle size Dv50 of the negative electrode main material is in the range of 5 to 20 μm; the negative electrode main material is selected from natural graphite, artificial graphite, mesophase carbon microspheres, hard carbon, soft carbon, silicon oxygen, silicon carbon and Li4Ti5O 12 One or more of .
11. The battery according to claim 1, characterized in that The electrolyte includes a solvent, and the solvent is selected from at least one of ethylene carbonate (EC), methylene methanedisulfonate (MMDS), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), propylene carbonate (PC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), cyclopentane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS), and diethyl sulfone (ESE).
Citation Information
Patent Citations
Electrolyte for silicon-carbon negative electrode and lithium ion battery
CN110994022A
Battery
CN115954543A
Secondary battery
CN117832614A